The Canyon's Edge - Bowling, Dusti (New York : Little, Brown and Company, 2020)
A year after the death of her mother in a restaurant shooting, Nora is left struggling to stay alive when a climbing trip with her father goes terribly wrong.
Keywords: Survival -- Juvenile fiction; Post-traumatic stress disorder -- Juvenile fiction; Hiking -- Juvenile fiction; Canyons -- Juvenile fiction; Families -- Juvenile fiction; Novels in verse; Survival -- Fiction; Post-traumatic stress disorder -- Fiction; Hiking -- Fiction; Canyons -- Fiction; Family life -- Fiction; Novels in verse; Novels in verse